Family-centered care of de newborn: perception of the multidisciplinar health team - Vargas , Ana Paula de Miranda (2022)
Descriptive exploratory study with a qualitative approach, aiming to reveal the perception of the multidisciplinary health team regarding care centered on the newborn's family. Conducted with 13 professionals from the multidisciplinary health team, through a semi-structured interview recorded by Google Meet and analysis of the discourses carried out by Minayo's referential, through which 3 context units emerged: Family-Centered Care: Considerations on Well-being Being of the Newborn; Family-Centered Care: Perceptions About Family Setup and Family-Centered Care: Concept or Intervention? Participants showed concern about teaching family members about care, instructing them on how the procedures should be performed, the correct technique to be performed, the proper posture within the hospital environment, listening to their demands and desires, and from the conversation and active listening implement their needs in direct and indirect assistance. The multidisciplinary team perceives the family as a pillar in the provision of care, but does not effectively consider its participation in the planning of care. The perception of the multidisciplinary team interviewed about Family-Centered Care is still fragile, showing little knowledge about this method of care.